Assessing fairness of CEO compensation and its implications on income inequality in Singapore - Cheong, Wei Qi (2019)
With increasing unhappiness about the widening income gaps between the rich and poor in Singapore, this paper takes the first step to look into the income of the country’s top earners and aims to evaluate the fairness and justifiability of such large pay gaps. Specifically the following questions are posed: 1. What are the main determinants of CEO compensation in Singapore; 2. Do these determinants affect CEO Compensation components (Fixed and Variable) differently; 3. What industrial effects are present for CEO compensation; 4. Are large income gaps between CEOs and average workers justifiable? i.e. are the gaps a result of efficient contracting or abuse of CEO power and government/state relationships? The first of its kind to investigate Chief Executive Officer (CEO) compensation empirically in Singapore, this paper utilizes the fixed effects Least Square Dummy Variable (LSDV) regression model to identify determinants of CEO compensation and included localized traits of Singapore. These traits include Singapore’s high dependency on global trade, presence of indirect corporate relationships of firms to the state, and the large population of family-managed firms. CEO compensation was analyzed in three forms - totality, fixed component, and variable component to give rise to a more holistic view on the channel to which the determinants affect compensation. Results show that while CEO compensation reflects efficient contracting of talents and efforts, there are signs of CEO power abuse and unfair government subsidies as well. To further investigate this, interaction effects of controversial determinants such as state relationships, family ties and CEO power are regressed. Results for state relationships show insignificant interaction effects but results for CEO power and family ties showed positive relationship with CEO compensation.